Effect of early rehabilitation on hospital stay and postoperative complications in elderly hip fracture patients: a prospective cohort study - Wen Tang; Yiqi Wang; Yulian He; Bo Liu; Runzhi Yuan; Yanhui Zhou; Huayong Huang (Journal of Orthopaedic Surgery and Research)
Abstract Background Hip fractures in the elderly are a major global public health concern, with incidence projected to rise as populations age. Rehabilitation is critical to recovery after hip fracture surgery, but the ideal timing for initiation remains uncertain. While early rehabilitation, within 48 h post-surgery, is associated with better outcomes, its specific impact on hospital stay duration and postoperative complications is not yet conclusively established. Aim This study aims to evaluate the effects of initiating rehabilitation within 48 h after hip fracture surgery on hospital length of stay and postoperative complications, compared to rehabilitation started one-week post-surgery in elderly patients. It is hypothesized that early rehabilitation will significantly reduce hospital stays and decrease the rate of postoperative complications. Methods In this prospective cohort study, patients aged 65 and older are divided into early rehabilitation (within 48 h) and delayed rehabilitation (after one week) groups. Data will be collected using electronic medical records (EMR), standardized clinical tools (Barthel Index, Timed Up and Go), and patient-reported outcome measures (SF-36, EQ-5D). Statistical analyses will include t-tests and chi-square tests for outcome comparison, with multiple regression adjusting for potential confounders such as age, gender, and comorbidities.